Gated streets: Neighborhood Councils and disputes in public spaces of Salamanca, Ate district, Lima-Peru - Navarro Céspedes, Hugo Alejandro (2019)
The article is part of a study carried out during the year 2013 in the urbanizations of Salamanca, district of Ate in the city of Lima. The objective is to understand the placement and permanency of gates in the streets and public spaces of these urbanizations. To this end, we sought to start from the controversies, which included gate-related issues, generated in the associations between the actors in order to describe the momentary stability of gated streets and public spaces. Finally, this description will allow us to incorporate, through a symmetrical perspective, other actors, agencies and groups with whom it is necessary to sit down, discuss and dialogue searching for a better coexistence.